2019
DOI: 10.3390/md18010021
|View full text |Cite
|
Sign up to set email alerts
|

Dual-Functioning Scaffolds for the Treatment of Spinal Cord Injury: Alginate Nanofibers Loaded with the Sigma 1 Receptor (S1R) Agonist RC-33 in Chitosan Films

Abstract: The present work proposed a novel therapeutic platform with both neuroprotective and neuroregenerative potential to be used in the treatment of spinal cord injury (SCI). A dual-functioning scaffold for the delivery of the neuroprotective S1R agonist, RC-33, to be locally implanted at the site of SCI, was developed. RC-33-loaded fibers, containing alginate (ALG) and a mixture of two different grades of poly(ethylene oxide) (PEO), were prepared by electrospinning. After ionotropic cross-linking, fibers were inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 22 publications
(21 citation statements)
references
References 58 publications
0
21
0
Order By: Relevance
“…RC-33 was synthetized and characterized, as described in [ 32 , 36 ]. Dialysis equilibrium studies were performed to investigate the polymer/drug interaction, in particular to quantify the amount of RC-33 bound to 1 mg of GG, as described by [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RC-33 was synthetized and characterized, as described in [ 32 , 36 ]. Dialysis equilibrium studies were performed to investigate the polymer/drug interaction, in particular to quantify the amount of RC-33 bound to 1 mg of GG, as described by [ 36 ].…”
Section: Methodsmentioning
confidence: 99%
“…In a previous work of ours, a dual-functioning scaffold for the local delivery of RC-33 was proposed as a combined approach, ensuring both neuroprotective and neuroregenerative outcomes, in the treatment of SCI [ 36 ]. In particular, RC-33-loaded nanofibers, based on alginate (ALG) and prepared by electrospinning, were incorporated in chitosan films to obtain a drug delivery system endowed with high flexibility, that was functional to an easy application at the injury site, and characterized by a controlled biodegradation rate.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently discovered a series of aryl aminoalkyl ketones endowed with good S1R binding affinity and antioxidant properties, as viable neuroprotective pharmacological tools [26]. Of note, the potent S1R agonist, called RC-33, identified in our lab is currently under investigation in vivo for its potential against Amyotrophic Lateral Sclerosis and for recovery of the damage of Spinal Cord Injury [21].…”
Section: Introductionmentioning
confidence: 99%
“…As a part of our current research [21][22][23][24][25], we have recently identified Sigma1 Receptor (S1R) modulators able to exert antioxidant activity in cellular models [17,24,[26][27][28]. S1R is a molecular chaperone residing at mitochondria-associated endoplasmic reticulum (ER) membrane [29].…”
Section: Introductionmentioning
confidence: 99%
“…Chitosan is the only cationic aminopolysaccharide in nature, and it is prepared by the N-deacetylation of chitin, a polymer that can be extracted from the exoskeleton of insects and crustaceans [4][5][6][7]. Due to the unique biological activity, chitosan has attracted sufficient attention in biotechnology, pharmaceutics, papermaking, wastewater, cosmetology, food science, agriculture, and textiles fields [8][9][10][11][12][13].…”
Section: Introductionmentioning
confidence: 99%